2019
DOI: 10.12998/wjcc.v7.i12.1444
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between circulating irisin levels and overweight/obesity: A meta-analysis

Abstract: BACKGROUND Currently, the findings about irisin as a novel myokine related to obesity are inconsistent in overweight/obese people. To our knowledge, no systematic analysis has been conducted to evaluate the relationship between irisin levels and overweight/obesity. AIM To evaluate the association between circulating irisin levels and overweight/obesity. METHODS The Cochrane Library, MEDLINE, SCOPUS, and the ISI Web of Science were searched to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
3
26
0
1
Order By: Relevance
“…The results in the present study revealed that there are high significant differences in each BMI, WC, FBS, insulin, HOMA-IR, and HOMA-B 2 between the normal weight group and obese group, suggesting that obesity has a role in impair of glucose-insulin homeostasis. Consistent with the previous study [ 8 , 12 ], there is a significant increase in the irisin level in the obese group compared to the normal weight group. The potential explanation could be because hypersecretion of irisin in the obese group is as a compensatory mechanism to combat irisin resistance in the obese [ 12 , 16 , 17 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results in the present study revealed that there are high significant differences in each BMI, WC, FBS, insulin, HOMA-IR, and HOMA-B 2 between the normal weight group and obese group, suggesting that obesity has a role in impair of glucose-insulin homeostasis. Consistent with the previous study [ 8 , 12 ], there is a significant increase in the irisin level in the obese group compared to the normal weight group. The potential explanation could be because hypersecretion of irisin in the obese group is as a compensatory mechanism to combat irisin resistance in the obese [ 12 , 16 , 17 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…FNDC5 is a type I trans-membrane protein which is predominantly present in cardiac and skeletal muscles and is secreted into the blood circulation [ 7 ]. Recently, a meta-analysis study found that the irisin level is higher in obese than normal weight individuals [ 8 ]. It is believed that irisin has a significant role in exercise-induced browning of white adipose tissues and stimulating the metabolic gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the included studies were performed in East Asia, India, and Egypt, and the generalizability of the findings is therefore limited. The association between serum irisin and DN in T2DM patients of other ethnicity, such as the Caucasians, should be determined in the future, since a potential ethnicity-difference in serum irisin level has been reported in previous studies including overweight/obesity population [44]. Besides, we chose eGFR of 60 ml/min as the cutoff value since most of the included studies reported the difference in serum irisin levels between DM patients with eGFR < or > 60 ml/min.…”
Section: Discussionmentioning
confidence: 99%
“…I risin -a novel, exercise-induced, myokine produced by proteolytic cleavage of fibronectin type III domain-containing 5 (FNDC5) -is mainly involved in the regulation of energy metabolism by activating thermogenesis to increase energy expenditure (1). In addition, it has been suggested that the myokine might be associated with glucose and lipid metabolism, insulin sensitivity (2), oxidative stress (3), and variations in body weight (4). Some reports demonstrated an association of irisin with systolic (SBP) (5-7) and diastolic (DBP) (5-8) blood pressure, but other yielded conflicting results (9,10).…”
Section: Introductionmentioning
confidence: 99%